Association between GPX1 Pro189Leu polymorphism and the occurrence of bladder cancer in Morocco - Hadami, K.; Ameziane El Hassani, R.; Ameur, A.; Dakka, N.; Abbar, M.; Al Bouzidi, A.; Attaleb, M.; El Mzibri, M. (Cellular and Molecular Biology, 2016)
Worldwide, Bladder cancer is the most frequent male malignancy. It is the third most common male malignancy in Morocco. The risk factors for developing bladder cancer are multiples including dietary conditions, environmental exposure and oxidative stress. GPX1 gene encoding for the human cellular antioxidant enzyme glutathione peroxidase1 is a key factor in the cell detoxification process. GPX1 Pro198Leu polymorphism is associated with a decrease of enzyme activity and may contribute to bladder cancer susceptibility. The present case-control study was planned to assess the presence of GPX1 Pro198Leu polymorphism in Moroccan population to determine whether it is associated with the risk of developing bladder cancer in Moroccan patients. A total of 32 patients with bladder cancer and 40 healthy controls were enrolled. Genotyping of the GPX1 Pro198Leu polymorphism was carried out by PCR amplification and DNA sequencing. Pro198Leu polymorphism was observed in both bladder cancer patients and healthy controls. No significant association between the polymorphism and bladder cancer occurrence was found (Pro/Leu vs. Pro/Pro: p=0.425; Leu vs. Pro: p=0.435). For the analysis of Pro198Leu polymorphism and progression of bladder cancer, no association was observed neither for stages (Pro/Leu vs. Pro/Pro: p=0.500; Leu vs. Pro: p=0.500) nor grades (Pro/Leu vs. Pro/Pro: p=0.415; Leu vs. Pro: p=0.427). Our results clearly showed no significant association between Pro198Leu polymorphism and risk of bladder cancer in our population, suggesting that the effect of this polymorphism on bladder cancer development might be a result of a combination with other genetic alterations and/or non-genetic variables such as diet and lifestyle factors.